Lepsze wrogiem dobrego? Ewolucja systemu wyborczego do sejmików województw w latach 1998-2002 - Alberski, Robert (Instytut Politologii Uniwersytetu Wrocławskiego, 2024)
The 1998 local government reform made regional assemblies and their boards, led by marshals, key political actors at the regional level. They have a significant impact on the economic and social development of the regions and the shaping of regional policy. Elections to the regional assemblies have become an important arena for political competition. The elections in 1998 and 2002 were conducted under different electoral systems, mainly differing in the shape and size of electoral districts. The electoral system favored large political entities due to small districts, the d'Hondt formula, and a relatively high electoral threshold. The reduction in the number of councilors in 2002 emphasized this trend, aiming to avoid excessive political fragmentation and ensure the stability of regional boards. The election results in 1998 and 2002 reflected these changes.
Keywords: regional policy; 1998 self-government reform in Poland; regional assemblies; electoral system; 1998 and 2002 regional assembly elections